Palimpsestes mémoriels : démantèlements et résurgences de deux monuments en Bulgarie postsocialiste - Belcheva, Ina (RACAR : Revue d'art canadienne / Canadian Art Review, 2021)
This article presents the case of an emblematic Bulgarian monument, 1300 Years Bulgaria, unveiled in Sofia in 1981: its fate during postsocialism until its dismantlement in 2017, and its replacement with an earlier war memorial that once stood at its approximate place. The conflict of memories represented by these destructions and substitutions is an occasion to question the way public narratives are constructed. This article focuses, in particular, on the instrumentalization of the aesthetic dimension in the memory and heritage debate. Through this case study, we analyze the way contemporary artistic practices influence the management of memories in public space. As such, artists play the role of memory mediators and producers of new artistic memories of Bulgarian socialism and postsocialism.